Hubungan Pola Asuh dengan Perkembangan Bahasa Anak Usia Pra-Sekolah di Sekolah Kristen Swasta Jakarta Barat: [The Relationship between Parenting Style and Language Development of Pre-School Age Children in West Jakarta Private Christian Schools] - Estahayati Sitompul; Amelia Kristanti Sapulette; Heny Dwi Astutik; Nungki Sri Handayani (Universitas Pelita Harapan, 2023)
Based on several recent studies, children's language development is closely related to parents' parenting patterns. Home and parents are the first ecological aspects for children's development. This research aims to prove these scientific (theoretical) claims. The method used was quantitative with a correlational research design, the number of respondents was 35 parents of K1 level at early childhood education West Jakarta Christian schools. Data were analyzed using Spearman correlation, validity using Product Moment and reliability using the Cronbach Alpha test for the Parenting Pattern variable and Cohen's Kappa for the language development variable. The research results showed that 35 parents of students used an authoritative parenting style, the calculated Rs calculation result was 0.2404 while the z table value at a significance of 0.05 was 1.96. Because the Z table is greater than the calculated Rs, it is concluded that there is no significant correlation between variable X (parental parenting) and variable Y (child's language development).